A Minimal Information Model for Potential Drug-Drug Interactions - Hochheiser, Harry; Jing, Xia; Garcia, Elizabeth A.; Ayvaz, Serkan; Sahay, Ratnesh; Dumontier, Michel; Banda, Juan M.; Beyan, Oya; Brochhausen, Mathias; Draper, Evan; Habiel, Sam; Hassanzadeh, Oktie; et al. (Frontiers in Pharmacology, 2021)
ions. A task force of the Semantic Web in Health Care and Life Sciences Community Group of the World-Wide Web consortium engaged informaticians and drug-drug interaction experts in in-depth examination of recent literature and specific potential interactions. A consensus set of information items was identified, along with example descriptions of selected potential drug-drug interactions (PDDIs). User profiles and use cases were developed to demonstrate the applicability of the model. Ten core information items were identified: drugs involved, clinical consequences, seriousness, operational classification statement, recommended action, mechanism of interaction, contextual information/modifying factors, evidence about a suspected drug-drug interaction, frequency of exposure, and frequency of harm to exposed persons. Eight best practice recommendations suggest how PDDI knowledge artifact creators can best use the 10 information items when synthesizing drug drug interaction evidence into artifacts intended to aid clinicians. This model has been included in a proposed implementation guide developed by the HL7 Clinical Decision Support Workgroup and in PDDIs published in the CDS Connect repository. The complete description of the model can be found at https://w3id.org/hclscg/pddi.